Original paperUnilateral thalamotomy for the treatment of tremor dominant Parkinson’s disease - Sobstyl, Michał; Ząbek, Mirosław; Koziara, Henryk; Kądziołka, Bartosz; Mossakowski, Zbigniew (Contemporary Oncology/Współczesna Onkologia, 2006)
Background and purpose: To assess the effectiveness of unilateral thalamotomy for the treatment of parkinsonian tremor and other motor signs of Parkinson’s disease (PD). Material and methods: Between 1999 and 2004, 41 patients with idiopathic tremor dominant PD were treated surgically in the Neurosurgical Department of Postgraduate Medical Center in Warsaw. Stereotactic thalamotomy was performed with Leksell stereotactic frame (model G) using intraoperative macrostimulation. The patients were assessed according to the Unified Parkinson’s Disease Rating Scale version 3. (UPDRS) before and after thalamotomy in the off state. The progression of PD was also evaluated according to the Hoehn and Yahr scale in the off state and also Schwab and England was used to assess the disability of the patients. The patients were evaluated before thalamotomy in the off state, and 3, 12, 24 and 36 months after surgery, according to the above mentioned clinical rating scales. Results: The authors report their results among 41 patients who underwent stereotactic thalamotomy 3 years postoperatively. At 3 years follow-up (in the group of 19 patients) the contralateral tremor from the presurgical value of 11.2 (items 20 – 21 UPDRS) decreased to 2.6. The rigidity in contralateral limbs at 3 years follow-up was 1.7 (item 22 UPDRS) when compared to 2.8 (item 22 UPDRS) preoperative value. Thalamotomy had no effect on bradykinesia or other manifestations of PD such as balance or gait disturbance. There were 13 transient and 6 permanent complications. Conclusions: Thalamotomy using intraoperative macrostimulation in carefully selected patients is a beneficial operation for the control of medically refractory parkinsonian resting and postural tremor. The effect of unilateral thalamotomy on tremor is long lasting.